Diurnal and day-to-day variations in isometric and isokinetic strength. (2nd November 2019) - Knaier, Raphael; Infanger, Denis; Cajochen, Christian; Schmidt-Trucksaess, Arno; Faude, Oliver; Roth, Ralf
ABSTRACT: Time-of-day effects in strength performance have been extensively investigated due to their relevance in competitive sports. However, most studies use large measurement intervals making it difficult to monitor potential performance changes throughout the day. Furthermore, previous studies have exclusively focused on how the time of day affects strength on a group level and ignored the individual differences in the times of peak performance. Therefore, the main purpose of this study was to investigate the diurnal and day-to-day variations in isometric and isokinetic leg, arm and trunk strength over six different times of the day. Following a familiarization test, 19 trained males (age: 24.1 ± 2.5 years) performed isometric and isokinetic strength assessments at six different times of the day (7:00, 10:00, 13:00, 16:00, 19:00, and 21:00) with an isokinetic dynamometer. An eighth test session was performed at the same time of the day as the seventh test session to investigate the day-to-day variations and the difference between diurnal and day-to-day variations were compared. All tests were separated by at least 48 h. The start time for the first session was randomized. The mean maximum isometric leg strength was 5.85 ± 0.80 N.kg −1 and 4.99 ± 0.78 N.kg −1 at the peak and at the nadir of the day, respectively. The mean difference (95% CI) was 0.86 ± 0.47 N.kg −1 (0.62; 1.10) for the diurnal variation and 0.30 ± 0.42 N.kg −1 (0.09; 0.52) for the day-to-day variation. The mean maximum isometric arm strength was 1.68 ± 0.33 N.kg −1 at the peak and 1.46 ± 0.19 N.kg −1 at the nadir of the day, respectively. The mean difference (95% CI) was 0.21 ± 0.16 N.kg −1 (0.14; 0.29) for the diurnal variation and 0.06 ± 0.05 N.kg −1 (0.03; 0.08) for the day-to-day variation. The linear mixed-effects model showed little evidence for differences in isometric leg strength between the different times of the day (all p -values >0.983). The present study demonstrated that diurnal variations in leg and arm strength are nearly three times higher than the day-to-day variations, but there was only little evidence for a time-of-day effect on a group level. The diurnal variations observed herein without time-of-day effects are suggestive that individuals achieve their peak performance at different times of the day. Therefore, performance tests should be carried out at the same time of the day to ensure comparability. Furthermore, depending on the difference between the time of competition and the time of peak performance, as well as the individual magnitude in diurnal variation, some athletes can have a clear disadvantage.Abbreviation : 95% CI, 95% confidence interval; SD, standard deviation; ICC, intraclass correlation coefficient.